The Seasonal and Spatial Distribution of Trichoptera Larvae in the Araç Creek (Kastamonu, Karabük, Turkey) - Küçükbasmaci, İbrahim; Findik, Özlem (Kastamonu University, 2020)
Aim of study: The larvae of different insect species are used to assess water quality at various pollution levels. The aim of this study was to determine the species composition and seasonal distribution of Trichoptera larvae of the Araç Creek and relation with physicochemical parameters. Area of study: Benthic macroinvertebrates were collected between April and October 2013 seasonally to determine the trichopteran species of the Araç Creek. Material and method: The samples were collected using a standard dip net (500µm). The trichopteran taxa were identified using Leica APO S8 binocular stereomicroscope. Environmental variables were measured in the field using portable instruments while total hardness was measured according to the standard analytical methods. Main results: Fifteen trichopteran taxa were identified from the Araç Creek. Three of them could be identified at the genus level. The maximum number of trichopteran larvae were collected at station 2 (311 individuals) while the fewest trichopteran were collected at station 6 (87 individuals). Hydropsyche botosaneanui was found to be the dominant species in Araç Creek. Research highlights: A total of 1223 larvae belonging to Trichoptera were collected from the Araç Creek. 15 taxa belonging to 9 genera of 8 different families (Brachycentridae, Hydropsychidae, Hydroptilidae, Lepidostomatidae, Leptoceridae, Limnephilidae, Psychomyiidae and Rhyacophilidae) were identified. The highest number of individuals was found in the spring season.
Keywords: Turkey; Trichopteran larvae; Trichoptera Larva; Araç Çayı; Kastamonu; Turkey; Kastamonu; Trichopteran Larvae; Araç Creek; Kastamonu; Turkey; Araç creek; 15. Life on land; 6. Clean water; 13. Climate action; 11. Sustainability; 14. Life underwater